A Case Series Hemichorea-Hemiballism Syndrome Related toNonketotic Hyperglycemia: A Challenge to Diagnostic Process - Sasiarini, Laksmi; Budianto, Rahmad; Tarigan, Ricky C. (Jurnal Penyakit Dalam Indonesia, 2019)
Diabetes mellitus is quite familiar to health-care personnel but occasionally presents with unusual manifestations. One of them is hemichorea-hemiballismus syndrome, a spectrum of involuntary, continuous non-patterned movement involving one side of the body which is related to nonketotic hyperglycemia in uncontrolled diabetes. Here we present two cases of nonketotic hyperglycemic diabetic patients who presented with the hemichorea-hemiballismus syndrome. First – a 57 years old woman was presented with involuntary, arrhythmic, and repetitive movement on the right arm and leg, accompanied by twitching on the right face for two weeks. She had an uncontrolled history of diabetes mellitus. The second- a 60 years old man was presented with recurrent general tonic-clonic seizure for about four days. The history of diabetes was unknown. Initial diagnosis on admission was general tonic-clonic seizure due to thrombotic cerebrovascular accident (CVA). Intravenous diazepam did not give any response to the seizures. Their brain CT scan imaging showed non-enhancing hyperdensities in the basal ganglia due to non-ketotic hyperglycemia, but the lesion was more extensive on the second patient. An involuntary movement was resolved after achieving blood glucose target by rehydration and continuous intravenous insulin therapy. Clinical response in these cases were reversible while the hyperdensities lesion will be persistent for a few months.